The PRIMA Study: presentation ischaemia-modified albumin in the emergency department. Issue 10 (20th September 2006) - Keating, L; Benger, J R; Beetham, R; Bateman, S; Veysey, S; Kendall, J; Pullinger, R
Abstract : Objectives: To investigate the diagnostic accuracy of presentation ischaemia-modified albumin (IMA), in addition to cardiac troponin I (TnI), as a strategy to rapidly ascribe low risk to patients with chest pain attending an emergency department, and to determine whether IMA has the potential to reduce transit time in emergency departments. Methods: A prospective observational study was carried out in two emergency departments (belonging to the John Radcliffe Hospital, Oxford, UK; and the Frenchay Hospital, Bristol, UK) of similar size. Consecutive adult patients presenting with features of possible ischaemic cardiac chest pain and a normal electrocardiogram were eligible. The index test (measurement of IMA and TnI at presentation) and reference standard (delayed TnI measurement, taken at least 8 h after pain onset) were applied to all recruited patients. All clinicians were blinded to the results of the index test. Assays were carried out in a single laboratory using standard techniques. Results: 399 patients were recruited; 277 patients had a result for both the index test and reference standard. The sensitivity was 97.6% (95% confidence interval (CI) 87.4 to 99.9), negative predictive value 97% (95% CI 84.2 to 99.9) and specificity 13.6% (95% CI 9.5 to 18.7). Sensitivity analysis showed similar findings in three alternative scenarios. Receiver operating characteristic analysis indicated that a different "cut-off" value for IMA would not improve the properties of the test. The median potential time saved (n = 268) was 6 h and 10 min. Conclusion: The diagnostic accuracy of presentation IMA in this study does not support its use as an effective risk stratification tool for patients with chest pain in the emergency department. The sensitivity is insufficiently high, with a small number of false negatives undermining the safety of the test. Frequent false positives produce a low specificity that limits the practical value of the test.